English Words in Context. An Unexpected Voyage: A Reading Adventure - Jenný Berglind Rúnarsdóttir 1966- (2016)
This paper is written in four parts and includes an introduction and a conclusion. The first part reviews the literature on the status of Icelandic English learners in primary schools in Iceland, the current Icelandic National Curriculum for Foreign Languages (2014), and the role of the European Language Portfolio as a tool for promoting learner autonomy. The wide gap between English learners in the primary school system and the requirements for digital literacy supports the growing need for effective CALL material, that are learner orientated. The second part of the paper is a review of research on different language methodologies and techniques that are relevant to the proposed learning material. Listening and vocabulary development is crucial to second language learning and the computer is an ideal tool to develop both, as well as, learner autonomy. The third part of the paper will describe the literature on vocabulary acquisition and developing listening skills. The literature is relevant to the methods, techniques, and content of the proposed computer assisted teaching material, An Unexpected Voyage: A Reading Adventure, which is aimed at developing vocabulary and listening comprehension within the context of a remedial interactive story at a pre-intermediate level. The final part of the paper is a discussion on the teaching material and its contents, the structure of the material, the objectives for the listening and vocabulary tasks, the plot outline, the characters and the setting, and how to implement in the classroom. It, moreover, discusses digital and teacher’s assessment and how the material relates to the Icelandic National Curriculum for foreign languages, the European Portfolio. And how the abilities listed in the CEFFL for study skills correlates to the teaching material. Finally, this paper will attempt to answer Chapelle’s questions on language learning potential related to this CALL material. Námsgagnastofnun Verkefnið er enn í vinnslu hjá menntamálastofnun og því er aðgangur læstur um ...